Handbook of research on using global collective intelligence and creativity to solve wicked problems emerging research and opportunities - Fields, Ziska, 1970- (IGI Global, 2020)
""This book explores 'why the many are smarter than the few' and the need and value of the collective intelligence and collective creativity of large globally formed groups of people to solve wicked global challenges"--Provided by publisher"--